PERANAN DEWAN KEHORMATAN IKATAN NOTARIS INDONESIA DALAM PENEGAKAN KODE ETIK NOTARIS DI KOTA MAKASSAR - , Irmawati Danumulya ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to examine how the role of Honorary Council of Indonesian Notaries Association in the enforcement of Notary Code of conduct in Makassar city after the Notary Act, and the authority of the Honorary Council of Indonesian Notaries Association of Makassar City in giving sanction its members who was convicted after a sanction imposed by the Regional Supervisor Assembly and the constraints faced by Honorary Council of Indonesian Notaries Association in the enforcement of the Notary Code of Conduct in Makassar City. The research is the empirical legal research, which the data used in this study is the primary and secondary data. Primary data obtained through interviews of respondents and interviewees. Secondary data obtained from the literature to get primary, secondary and tertiary legal materials. Overall the data obtained and analyzed qualitatively. Based on the results showed Indonesian Notaries organization still has a role in enforcing the Notary code of conduct in Makassar city after the Notary Act, in which the enforcement of Notary codes of conduct internally done by the Honorary Council, while the external enforcement relating to notary behavior and his position made by the Supervisor Assembly. Honorary Council of Indonesian Notaries Association of Makassar city still has the authority to sanction members who were found guilty after a sanction imposed by the Regional Supervisor Assembly, which is based on the INI article of association Article 19 paragraph (8) is given a warning of sanctions in the form of both written and verbal to Notary who violates the internal Code of conducts. Constraints faced by Honorary Council of Indonesian Notaries Association in the enforcement of the Notary Code of conducts in Makassar city are violations that have been considered to be a habit by the Notary, the lack of understanding about the code of conduct, a sense of reluctant to colleagues to reprimand or impose sanctions.